2004
DOI: 10.1023/b:neab.0000038130.04373.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electrical Stimulation of the Paleocerebellar Cortex on Penicillin-Induced Convulsive Activity in Rats

Abstract: Studies in Wistar rats in conditions of free behavior showed that low-frequency stimulation of the paleocerebellar cortex (nodulus, uvula) (10-12 Hz, 0.5 msec) was accompanied by activation of spike discharges induced by systematic application of benzylpenicillin sodium (3,000,000 IU/kg). Facilitation of the formation of ictal discharges was also seen. High-frequency electrical stimulation (100-300 Hz, 0.25 msec) of the same structure was accompanied by suppression of the generation of spike potentials and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…18,54,55,60 It seems that there is a consensus regarding the charge density and the low-frequency stimulation used in human studies. 19,55,56,61 A significant confounding factor in the evaluation of the CS studies in humans is the inclusion of patients with epilepsy of various origins and different seizure patterns. [8][9][10][11]18,34,54,55,60 It is very unlikely that medically intractable epilepsy secondary to dysplastic changes and epilepsy due to the presence of vascular pathological features would respond to CS of standard parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, stimulation parameters were not standardized in these experiments. A recent publication supports the antiepileptic effect of high frequency (100–300 Hz) paleocerebellar stimulation in rats treated with benzylpenecillin sodium; an effect that was exacerbated using low‐frequency (10–12 Hz) stimulation (22). The relatively few new animal studies published over the last decade indicate that interest in cerebellar stimulation for epilepsy is fading (see Myers et al.…”
Section: Deep Brain Stimulation Of the Epilepsy Control Systemsmentioning
confidence: 95%
“…Stimulation of the paramedian lobule at 300 Hz (Cooke and Snider, 1955;Iwata and Snider, 1959), and also the fastigial deep nucleus, inhibited electrically induced seizures in cortex and hippocampus. Benefits of cerebellar stimulation depended upon the frequency of stimulation (Godlevskii et al, 2004): stimulation of the nodulus at about 10 Hz in rats increased epileptiform discharges, whereas 100-300 Hz decreased discharges. Several subsequent animal studies showed favorable effects of surface or deep cerebellar stimulation on inhibiting seizures in animal models (Dow et al, 1962;Hutton et al, 1972;Babb et al, 1974;Strain et al, 1978).…”
Section: Cerebellar Stimulation For Epilepsymentioning
confidence: 99%